2006
DOI: 10.1364/oe.14.004552
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive optics flood-illumination camera for high speed retinal imaging

Abstract: Current adaptive optics flood-illumination retina cameras operate at low frame rates, acquiring retinal images below seven Hz, which restricts their research and clinical utility. Here we investigate a novel bench top flood-illumination camera that achieves significantly higher frame rates using strobing fiber-coupled superluminescent and laser diodes in conjunction with a scientific-grade CCD. Source strength was sufficient to obviate frame averaging, even for exposures as short as 1/3 msec. Continuous frame … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
100
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(102 citation statements)
references
References 23 publications
1
100
0
Order By: Relevance
“…First applied to a conventional fundus camera by Liang et al, 1 AO has been subsequently applied to confocal laser scanning ophthalmoscopes [2][3][4] and most recently to optical coherence tomography. [5][6][7] Such systems have enabled cone classing of individual photoreceptors, 8,9 measurement of the directionality of individual cones, 10 the temporal 11,12 and wavelength properties 13 of cone reflectance, and the characterization of the cone mosaics in forms of sex linked dichromacy. 14 Recently, Choi et al 15 and Wolfing et al 16 have shown cone loss in retinal dystrophies and correlations with retinal function.…”
Section: Introductionmentioning
confidence: 99%
“…First applied to a conventional fundus camera by Liang et al, 1 AO has been subsequently applied to confocal laser scanning ophthalmoscopes [2][3][4] and most recently to optical coherence tomography. [5][6][7] Such systems have enabled cone classing of individual photoreceptors, 8,9 measurement of the directionality of individual cones, 10 the temporal 11,12 and wavelength properties 13 of cone reflectance, and the characterization of the cone mosaics in forms of sex linked dichromacy. 14 Recently, Choi et al 15 and Wolfing et al 16 have shown cone loss in retinal dystrophies and correlations with retinal function.…”
Section: Introductionmentioning
confidence: 99%
“…The use of adaptive optics made it possible for a dynamic, highspeed correction of the eye's aberrations in any fundus imaging device, from the simple fundus camera [4][5][6], to the confocal scanning laser ophthalmoscope (cSLO) [7][8][9] or the optical coherence tomography (OCT) [10,11]. Moreover, the idea of a deconvolution of the fundus image with the measured wavefront was also suggested as a method of enhancing image quality [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, adaptive optics (AO) has been demonstrated as an indispensable highresolution enabler for a variety of ophthalmic imaging modalities, including adaptive optics flood illumination funds camera [1][2][3][4], adaptive optics scanning laser ophthalmoscope (AOSLO) [5][6][7], and adaptive optics optical coherence tomography (AOOCT) [8][9][10][11]. AO facilitates ophthalmic imaging in two aspects.…”
Section: Introductionmentioning
confidence: 99%
“…In general, to achieve a bandwidth of 30 Hz (0-dB bandwidth of the error transfer function), the AO should operate with a loop frequency at least 90 Hz, i.e., at least 3 times of the highest temporal frequency of the ocular wave aberration [14,22]. However, in most AO retinal imaging systems, the loop frequency is less than 30 Hz [2,4,6,7,[9][10][11][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. While AO operated with low speed has enabled important discoveries in basic science and clinical research, question about the necessity or the benefit of high speed AO for retinal imaging remains to be addressed.…”
Section: Introductionmentioning
confidence: 99%